Mechanical properties of thermoplastic cassava starch/ coconut fibre composites: Effect of fibre size - Jumaidin, Ridhwan; Gazari, Ainin Sofiya; Kamaruddin, Zatil Hafila; Kamaruddin, Zatil Hazrati; Zakaria, Nazri Huzaimi; Abdul Kudus, Syahibudil Ikhwan; Yob, Mohd Shukri; Abd Munir, Fudhail; Keshavarz, Meysam (Universiti Putra Malaysia Press, 2024)
This research aims to study the thermal and mechanical properties of biodegradable thermoplastic cassava starch (TPCS) reinforced with various sizes of coconut husk fibre (CHF). The range of fibre sizes used was 125, 200, and 300 μm. These CHFs were integrated into a thermoplastic cassava starch matrix to make bio-composites. After integrating all components, the bio-composites were hot-pressed at 155°C for 60 minutes to produce thermoplastic sheets. Tensile and flexural tests were carried out to examine the mechanical characteristics of TPCS/CHF composites. The samples were also characterised using Thermogravimetric Analysis (TGA), X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy (SEM). The findings demonstrated that a smaller 125 μm CHF improved the mechanical properties higher than other fibre sizes. Fibre with 300 μm showed more voids, which led to lower material strength. TGA results showed that 300 μm fibres enhanced the crystallinity and thermal stability of the material. FTIR and TGA showed that CHF incorporation increased intermolecular interactions and thermal stability. Overall, a smaller fibre size of 125 μm showed a better reinforcement effect than the larger fibre sizes, which enhanced the materials’ tensile and flexural properties. This study demonstrated that modified TPCS/ CHF has shown enhanced functionality than neat TPCS